A Comprehensive Overview of Traditional Indigenous Foods in Canada: Analysis of Grey Literature and Public Information Sources - Camryn Desjarlais; Juliana Meneghetti; Elder Darcey Sedgwick; Annalijn I. Conklin (International Journal of Environmental Research and Public Health, 2026)
Land-based Indigenous food practices are integral to cultural identity and ancestral knowledge, and provide medicine for health and wellbeing. We surveyed Indigenous-specific grey literature, guided by Elder knowledge, from public information sources to identify the scope of Indigenous traditional foods in Canada and how food use aligned with major food groups. We analyzed extracted data using summary statistics and graphical display. We identified 96 resources reporting 401 distinct food items incorporated into Indigenous food practices across Canada. Prevalent food groups were meat/proteins (39%), vegetables (20%), berries/fruits (12%), and a mixed group (21%); grains were rarely reported (1%). We found 28 unique plant foods reported to have multiple uses. Across sources, the top 15 most common food items were various berries, fish and wild game. The total count of food items and diversity with food groups categories varied by Indigenous group and region. This research documents the breadth and depth of traditional Indigenous food knowledge throughout Canada, demonstrating a consumption pattern focused on wild meat, berries and foods from plant and tree leaves, roots and stems. This overview of Indigenous food knowledge can support Indigenous individuals and communities, researchers and healthcare providers to improve health and wellbeing of Indigenous people.